Сравнительный анализ нематодофауны крестовника ромболистного (Senecio rhombifolius W.) первого и третьего годов вегетации - Павлюк, Л.В. (Вестник зоологии, 1972)
57 species of Nematoda, representatives of 4 ecological groups, are registered in Senecio rhombiculis Mill. Ectoparasite Paratylenchus nanus predominates in soil under one-year and three-year plants and in their roots. Under conditions of monoculture the total quantity of worms grows with the age of the plant and a definite biocenosis is formed with the predominance of their several secies.